2009
DOI: 10.1111/j.1439-0426.2009.01231.x
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight relationships for 12 fish species caught in Seyhan Dam Lake in southern Anatolia, Adana, Turkey

Abstract: Presented are the length-weight relationships of 12 fish species

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 3 publications
(3 reference statements)
0
8
0
Order By: Relevance
“…Table 1 presents the sample size, the minimum and maximum TL and W measurements for each species, the TL-W relationships, parameters a and b, the standard error of the slope and the coefficient of determination r 2 . The expected range of 2.5<b<3.5 (Froese, 2006) Ergüden and Göksu (2009) have published reports about the length-weight relationship parameters of some of the freshwater fish species in inland waters of Turkey. Tarkan et al (2006) reported positive allometric growth for A. boyeri, C. gibelio, R. amarus, V. vimba in Marmara region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 presents the sample size, the minimum and maximum TL and W measurements for each species, the TL-W relationships, parameters a and b, the standard error of the slope and the coefficient of determination r 2 . The expected range of 2.5<b<3.5 (Froese, 2006) Ergüden and Göksu (2009) have published reports about the length-weight relationship parameters of some of the freshwater fish species in inland waters of Turkey. Tarkan et al (2006) reported positive allometric growth for A. boyeri, C. gibelio, R. amarus, V. vimba in Marmara region.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, silver gold fish (Carassius gibelio) was stated in the lake but the price is not as good as for other commercial fishes despite the important production from the lake. There are some studies for weight-length relationship (LWR) regarding fish species in freshwater of different geographic regions in Turkey (Tarkan et al, 2006;Torcu-Koç et al, 2006;Ergüden and Göksu, 2009;lhan et al, 2012). Data of LWR in fishes could be useful to estimate the biomass of a fish species from their length observations for yield assesment (Froese, 1998;García et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The variation in the exponent (b) of the length weight Table 2. The parameters of the length-weight relationships of 9 species belonging to 4 different genus together with the regression coefficient (r 2 ), the number of specimens (n), minimum (min), maximum (max), mean ± standard error of the total length and 95% Confidence Interval b(±SE) of specimens measured and statistical results relationships of fish species could be affected by geographic locations, sampling area, seasons, sex, spawning time, sexual maturity, stomach fullness, size range and ecological factors such as temperature (Yılmaz and Polat, 2009;Erguden and Goksu, 2009;Ayyildiz et al, 2014). Different species belonging to the same genus can possibly affect the b value (Ayyildiz et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…07p7 the value calculated for the whole sample was similar to (Altindag et al, 2002), or higher than those reported in the literature (O'maoileidigh and Bracken, 1989;Wright and Giles, 1991;Altindag et al, 1998;Sinis et al, 1999;Miranda et al, 2006;Alaş and Ak, 2007;Balık et al, 2009;Erguden and Goksu, 2009;Erguden and Goksu, 2010;Innal, 2010). The tench in Trasimeno Lake can reach the length of 50.54 cm and the rate of growth was high (0.27 yr −1 ); also the growth performance index testifies the quality of the growth, being its value the higher reported in literature for other populations (Wright and Giles, 1991;Balık et al, 2009;Froese and Pauly, 2011).…”
Section: Discussionmentioning
confidence: 52%